Biocatalyzed Flow Oxidation of Tyrosol to Hydroxytyrosol and Efficient Production of Their Acetate Esters - Francesca Annunziata; Martina L. Contente; Cecilia Pinna; Lucia Tamborini; Andrea Pinto (MDPI AG, 2021)
Tyrosol (Ty) and hydroxytyrosol (HTy) are valuable dietary phenolic compounds present in olive oil and wine, widely used for food, nutraceutical and cosmetic applications. Ty and HTy are endowed with a number of health-related biological activities, including antioxidant, antimicrobial and anti-inflammatory properties. In this work, we developed a sustainable, biocatalyzed flow protocol for the chemo- and regio-selective oxidation of Ty into HTy catalyzed by free tyrosinase from Agaricus bisporus in a gas/liquid biphasic system. The aqueous flow stream was then in-line extracted to recirculate the water medium containing the biocatalyst and the excess ascorbic acid, thus improving the cost-efficiency of the process and creating a self-sufficient closed-loop system. The organic layer was purified in-line through a catch-and-release procedure using supported boronic acid that was able to trap HTy and leave the unreacted Ty in solution. Moreover, the acetate derivatives (TyAc and HTyAc) were produced by exploiting a bioreactor packed with an immobilized acyltransferase from Mycobacterium smegmatis (MsAcT), able to selectively act on the primary alcohol. Under optimized conditions, high-value HTy was obtained in 75% yield, whereas TyAc and HTyAc were isolated in yields of up to 80% in only 10 min of residence time.